Acupuncture for Cancer Pain and Symptom Management in a Palliative Medicine Clinic. (April 2019) - Miller, Katherine R.; Patel, Jai N.; Symanowski, James T.; Edelen, Connie A.; Walsh, Declan
Objective: Studies suggest acupuncture improves cancer-related symptoms; however, it is unclear whether patient characteristics predict pain response. This study determined acupuncture's effect on cancer-related pain and identified variables associated with pain response. Methods: A retrospective chart review included adult patients with cancer referred to palliative medicine and received acupuncture for pain management. Paired t tests compared differences in pain scores from pre- to postacupuncture. Clinically meaningful pain improvement was defined as ≥2-point reduction in pain score. Logistic regression was used to evaluate associations between patient characteristics and pain improvement. Results: One hundred seventy acupuncture treatments from 68 individual patients were studied. Significant reductions in mean pain scores were observed after the first treatment (−1.9 ± 1.8; P < .001) and across all treatments (−1.7 ± 1.9; P < .001). Multivariable analysis demonstrated clinically meaningful pain improvement with higher baseline pain scores (odds ratio [OR]: 1.79, 95% confidence interval [CI]: 1.44-2.22; P < .001) and stage III/IV disease (OR: 3.23, 95% CI: 1.11-9.40; P < .001). There were significant improvements in anxiety, depression, drowsiness, dyspnea, fatigue, nausea, and well-being after the first treatment and across all treatments ( P < .001). Conclusions: Acupuncture improved cancer-related pain and other symptoms. Those with higher baseline pain scores and advanced disease were more likely to achieve significant pain reduction. Improved depression and fatigue were closely related to pain reduction. Further studies are needed to confirm pain response variables, establish durability, and develop a personalized approach to acupuncture.